Single-port access laparoscopic re-staging with bilateral salpingo-oophorectomy and bilateral pelvic lymph node dissection for endometrial cancer - Xiaohui Ong; Elisa Koh; Timothy Yong Kuei Lim (Wolters Kluwer Medknow Publications, 2014)
Laparo-endoscopic single site surgery (LESS) is a relatively new technique that has been described in recent medical literature to be feasible in the management of benign gynaecological conditions. However, the use of this technique in the management of gynaecological cancers is still controversial. In this case report, we describe the first single port laparoscopic pelvic lymphadenectomy performed in Singapore. This involved a patient who was diagnosed with endometrial cancer after a vaginal hysterectomy for uterovaginal prolapse.